PEMBELAJARAN OPEN-ENDED UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA (PENELITIAN EKSPERIMEN PADA SISWA KELAS IVSDN 034TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR) (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The main purpose of this research was to obtain an overview of the increase in problem solving ability mathematics students who are learning to approach open-ended when compared to conventional learning, student responses to the instructional approach to open-ended undertaken, as well as the activities of students and teachers in the learning approach to open -ended. The design of this study is the experimental design called delayed counter balanced design . In this study, the experimental group gained learning with open-ended approach and gain control group of conventional learning. To get the research data used instrument in the form of mathematical problem solving ability test, students attitudes scale and observation sheet. Subjects were students of SDN 034 Tarai BangunKecamatan TambangKabupaten Kampar with the subject sample were fourth grade students selected by purposive sampling technique. Based on data analysis, found that the increase in mathematical problem-solving ability to get learning with open-ended approach is significantly higher than students who received conventional learning. Students have a positive attitude about learning open-ended. Activities of students and teachers during learning with an open-ended approach going well and conducivekey words:open-ended, mathematical problem solving ability